From Mystique to Muddle: Unresolved Logic in Joko Anwar's Series - Nuswantoro, Fajar (Universitas Multimedia Nusantara, 2025)
Television series, as narrative mediums, rely on the audience’s ability to suspend disbelief to emotionally and intellectually engage with fictional worlds. This study examines the